Coupling of economic growth and reduction in carbon emissions at the efficiency level: Evidence from China. (15th December 2020) - Sheng, Pengfei; Li, Jun; Zhai, Mengxin; Huang, Shoujun
Abstract: Our work provides a comprehensive investigation of the coupling between the efficiency of economic growth and the efficiency of carbon emissions reduction in China, and makes a distinction between the coupling over the long-run and the short-run. Our estimates suggested significant evidence of coupling between economic growth and efficiency in carbon emissions reduction in the long-run, but China's economic growth still increased carbon emissions at the aggregate level. In the short-run, coupling effects were different across provinces that were at different stages of economic development. Provinces with low- and high-stages of development saw positive short-run coupling, but provinces at the intermediate stage of development saw the contrary, which resulted in an obvious "U" shaped relationship between short-run coupling effects and real GDP per capita. Finally, our findings provide an economic rationale for differentiated low-carbon policies. Highlights: Coupling Economic Growth with Carbon Emissions Reduction at the Efficiency Level. Making a distinction between the coupling in the long-run and that in the short-run. Over the period 1997–2017, we saw evidence of the long-run coupling. The Short-run coupling varies across different provinces.